2019
DOI: 10.1200/jco.19.00201
|View full text |Cite
|
Sign up to set email alerts
|

Local Consolidative Therapy Vs. Maintenance Therapy or Observation for Patients With Oligometastatic Non–Small-Cell Lung Cancer: Long-Term Results of a Multi-Institutional, Phase II, Randomized Study

Abstract: PURPOSE Our previously published findings reported that local consolidative therapy (LCT) with radiotherapy or surgery improved progression-free survival (PFS) and delayed new disease in patients with oligometastatic non–small-cell lung cancer (NSCLC) that did not progress after front-line systemic therapy. Herein, we present the longer-term overall survival (OS) results accompanied by additional secondary end points. PATIENTS AND METHODS This multicenter, randomized, phase II trial enrolled patients with stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
772
5
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,028 publications
(873 citation statements)
references
References 22 publications
21
772
5
11
Order By: Relevance
“…In many kinds of cancers, oligometastasis is an independent prognostic factor, including NPC . Some studies have shown that after systemic therapy, patients with oligometastasis can reach more than 5 years of progress‐free survival . Oligometastasis is recognized as an early stage of cancer progression, at which point the invasiveness is still weak, as evidenced by the low number of metastases and a limited number of organs affected .…”
Section: Discussionmentioning
confidence: 99%
“…In many kinds of cancers, oligometastasis is an independent prognostic factor, including NPC . Some studies have shown that after systemic therapy, patients with oligometastasis can reach more than 5 years of progress‐free survival . Oligometastasis is recognized as an early stage of cancer progression, at which point the invasiveness is still weak, as evidenced by the low number of metastases and a limited number of organs affected .…”
Section: Discussionmentioning
confidence: 99%
“…Three randomized controlled trials reported improved overall survival in lung cancer (Gomez et al, 2019) , and a disease agnostic setting ; the fourth study was underpowered for overall survival but reported a significantly improved progression-free survival (Iyengar et al, 2018): The results regarding NSCLC are summarized in Table 1. Whereas radiofrequency ablation was the exclusive locally ablative treatment modality in the earliest CLOCC trial (Ruers et al, 2017), SBRT was the exclusive locally ablative treatment modality in two studies (Iyengar et al, 2018;Palma et al, 2019) and the most frequent in one study (Gomez et al, 2019). Therefore, the current ESMO guideline for oligometastatic NSCLC states that the 'relative contribution of surgery versus radiotherapy as local treatment modality has not been established yet' in OMD.…”
Section: Technology To Advance Cancer Care: the Example Of Sbrt For Omentioning
confidence: 99%
“…Oligometastatik meme ve prostat kanserinde ortanca sağkalım 36 ayları bulabilmektedir (13,14). Bu durumda metastaz bölgesine küratif amaçlı ablatif RT uygulanır (15).…”
Section: Kemik Metastazlarıunclassified